PEMANFAATAN PRODUK TURUNAN RAGI ROTI SEBAGAI SUPLEMEN MEDIA DEDAK PADI TERHADAP PERTUMBUHAN LARVA Hermetia illucens DAN KUALITAS KASGOT - Nurita Thiasari (BIOLOVA, 2026)
Black soldier fly (Hermetia illucens) larvae have considerable potential as agents for bioconversion of organic waste into high-protein biomass and frass that can be utilized as organic fertilizer. This study evaluated the effect of baker’s yeast (Saccharomyces cerevisiae) derivative supplementation in rice bran medium on larval growth and frass quality. A completely randomized design (CRD) with six treatments and four replications was employed. Treatments consisted of rice bran without supplementation (P0) and rice bran supplemented with yeast derivatives at levels of 1% (P1), 2% (P2), 3% (P3), 4% (P4), and 5% (P5). Observed parameters included fresh larval weight, larval body length, and frass dry matter (DM) and organic matter (OM) contents. The results demonstrated that yeast supplementation significantly (P<0.05) increased fresh larval weight and body length compared with the control. However, no significant effects (P>0.05) were observed on frass DM and OM contents. In conclusion, baker’s yeast derivatives can be applied as feed media supplements to enhance the growth performance of H. illucens larvae reared on rice bran without markedly altering frass quality.